Using the equation cos(a+b) = cos(a)cos(b) - sin(a)sin(b) or otherwise, show that cos(2x) = 2cos^2(x) - 1.

First let a = b = x such that:          

          cos(a + b) = cos(a)cos(b) - sin(a)sin(b)

becomes:

          cos(x + x) = cos(x)cos(x) - sin(x)sin(x)

Leading to:

          cos(2x) = cos2(x) - sin2(x)

Using the fact that sin2(y) + cos2(y) = 1 or rearranged sin2(y) = 1 - cos2(y):

          cos(2x) = cos2(x) - (1 - cos2(y)) = 2cos2(x) - 1, as required.

Another suitable approach may involve the Maclaurin series of cos(2x) and cos2(x) to arrive at the required relation, although this is more involved.

Answered by Benjamin H. Maths tutor

3124 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What does it mean for a function to have one to one mapping?


Let w, z be complex numbers. Show that |wz|=|w||z|, and using the fact that x=|x|e^{arg(x)i}, show further that arg(wz)=arg(w)+arg(z) where |.| is the absolute value and arg(.) is the angle (in polar coordinates). Hence, find all solutions to x^n=1 .


Express (16x^2 + 4x^3)/(x^3 + 2x^2 - 8x) + 12x/(x-2) as one fraction in its simplest form.


Calculate dy/dx for y=x(x−1)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences